2013
DOI: 10.1002/2013jd019803
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen isotope signatures preserved in tree ring cellulose as a proxy for April–September precipitation in Fujian, the subtropical region of southeast China

Abstract: A tree ring cellulose oxygen isotope (δ18O) chronology for the period 1870–2011 was established using samples from four Fokienia hodginsii trees with the aim of exploring the potential to use tree ring δ18O records to reconstruct climatic variations in Fujian, a subtropical region of southeast China. We believe that this is the first tree ring δ18O chronology from this area. Response analysis revealed that tree ring δ18O is significantly correlated with precipitation between April and September, relative humid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 68 publications
7
55
0
Order By: Relevance
“…2 and 3). The modified plate method (Kagawa et al, 2015;Xu et al, 2011Xu et al, , 2013b, based on the chemical treatment procedure of the Jayme-Wise method (Green, 1963;Loader et al, 1997), was used to extract α-cellulose. The plate method of extracting α-cellulose directly from the wood plate rather than from individual rings can reduce the α-cellulose extraction time .…”
Section: Cellulose Extraction Isotope Measurement and Chronology Devmentioning
confidence: 99%
See 2 more Smart Citations
“…2 and 3). The modified plate method (Kagawa et al, 2015;Xu et al, 2011Xu et al, , 2013b, based on the chemical treatment procedure of the Jayme-Wise method (Green, 1963;Loader et al, 1997), was used to extract α-cellulose. The plate method of extracting α-cellulose directly from the wood plate rather than from individual rings can reduce the α-cellulose extraction time .…”
Section: Cellulose Extraction Isotope Measurement and Chronology Devmentioning
confidence: 99%
“…The plate method of extracting α-cellulose directly from the wood plate rather than from individual rings can reduce the α-cellulose extraction time . In addition, the modified plate method can reduce the amount of sample material lost during cellulose extraction, enabling sufficient material to be obtained to enable narrow rings to be measured by isotope ratio mass spectrometer (Xu et al, 2013b). There is no statistically significant difference between tree-ring δ 18 O values obtained by the plate and conventional methods (Kagawa et al, 2015;Xu et al, 2013b).…”
Section: Cellulose Extraction Isotope Measurement and Chronology Devmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether or not the apparent rings of F. semicordata are annual in nature, we analyzed tree ring oxygen isotopes of the two cores in the apparent rings. We can assume that tree ring cellulose δ 18 O of the two trees should be highly correlated if the apparent rings of F. semicordata are actual annual rings, based on previous studies of tree ring cellulose δ 18 O of Fokienia hodginsii from northern Laos, Vietnam and southern China (Sano et al, 2012;Xu et al, 2011Xu et al, , 2013aXu et al, , 2013b. We measured 50 and 184 rings for Ka-018 and Ka-019, respectively.…”
Section: Sampling Site and Local Climatementioning
confidence: 99%
“…Therefore, tree ring oxygen isotope series can potentially record the amount of rainfall in areas where the amount effect occurs. Previous studies have shown that tree ring oxygen isotopes reflect regional rainy season precipitation in Laos [ Xu et al ., ], Thailand [ Xu et al ., ], Bhutan [ Sano et al ., ], and Fujian, a subtropical region of southeast China [ Xu et al ., ]. In this study, we analyzed the tree ring cellulose oxygen isotopes preserved in young and old P. taiwanensis from the lower reaches of the Yangtze River in southeast China over the period of 1850–2013, at both annual and seasonal resolution, and explore the potential utility of tree ring cellulose δ 18 O in reconstructing precipitation records.…”
Section: Introductionmentioning
confidence: 99%